2016
DOI: 10.3847/0004-637x/824/2/128
|View full text |Cite
|
Sign up to set email alerts
|

Helioseismic Imaging of Supergranulation Throughout the Sun’s Near-Surface Shear Layer

Abstract: We present measurements of the Sun's sub-surface convective flows and provide evidence that the pattern of supergranulation is driven at the surface. The pattern subsequently descends slowly throughout the near-surface shear layer in a manner that is inconsistent with a 3D cellular structure. The flow measurements are obtained through the application of a new helioseismic technique based on traditional ring analysis. We measure the flow field over the course of eleven days and perform a correlation analysis be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 64 publications
5
29
1
Order By: Relevance
“…The absence of stronger latitudinal variations of the mean solar photospheric intensity could then be explained by the fact that convective flows are probably not rotationally constrained anymore in the nearsurface shear layer that spans the outermost 35 Mm of the Sun (Greer et al 2016a,b). Greer et al (2016a) suggest weak rotational constraint in the outer layers above r ≈ 0.96r o , while we find for the thin shell model displayed in Fig. 2d that the transition Ro = 1 occurs at r ≈ 0.9r o -a value which is slightly lower than the one predicted from observations, but we may have deeper transitions in numerical models given the much lower density stratification of the convective zone.…”
Section: Resultscontrasting
confidence: 61%
“…The absence of stronger latitudinal variations of the mean solar photospheric intensity could then be explained by the fact that convective flows are probably not rotationally constrained anymore in the nearsurface shear layer that spans the outermost 35 Mm of the Sun (Greer et al 2016a,b). Greer et al (2016a) suggest weak rotational constraint in the outer layers above r ≈ 0.96r o , while we find for the thin shell model displayed in Fig. 2d that the transition Ro = 1 occurs at r ≈ 0.9r o -a value which is slightly lower than the one predicted from observations, but we may have deeper transitions in numerical models given the much lower density stratification of the convective zone.…”
Section: Resultscontrasting
confidence: 61%
“…This is consistent with the findings by Shine et al (2000) who observed several individual supergranules forming in LCT divergence maps obtained from Michelson Doppler Imager (Scherrer et al 1995) intensity images. The sign reversal of the horizontal divergence after about two days was also observed by Greer et al (2016) using helioseismic ring-diagram analysis (see Figs. 7 and 8a therein).…”
Section: The Average Supergranulesupporting
confidence: 68%
“…Typically, vertical variations can be evaluated down to 10-15 Mm below the surface, but the accuracy of measurements deeper than 10 Mm is still debated. A comparison between the tracking and helioseismic reconstructions of large-scale solar surface flows, showing good agreement between the two, can be found for instance inŠvanda et al (2007) and Greer et al (2016).…”
Section: Local Helioseismologysupporting
confidence: 56%